EFFECTIVITY OF FEEDING FISH FLOUR ON DAPHNIA SP. TO INCREASE GROWTH PERFORMANCE AND SURVIVAL RATE GOURAMY LARVAE (Osphronemous gouramy - Tri Ayu Lestari; Siti Hudaidah; Limin Santo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
The aim from this study is to find out the addition of natural feeds of Daphnia sp. that given of fish flour to the growth performance and survival rate of osphronemus gouramy larva. this study was conducted on July – August 2019 in Freshwater Aquaculture Development (FAD) Natar, east Lampung. The experimental method was used Complete Random Design (CRD) which 4 treatments and three replications on each. The treatments applied in this study were whithout fish meal feed (control), fish meal 2 gram, fish meal 4 gram and fish meal 6 gram. The highest protein content of the proximate test result is found in Daphnia sp. with dose 6 gram that containt of protein 7,64% and the lowest was found in whithout fish meal feed (control) containt of protein 4,58%. The results shiwed that Daphnia sp. those fed with fish meal were significantly different or had on effect on growth performance gouramy larvae, but had no effect on survival rate of gouramy larvae.